Vapour phase methylation of phenol over nanocrystalline ZnFe(2-x)A1(x)O(4) (x=0, 0.25, 0.5, 0.75 and 1.0) ferrospinel system - Reddy, Vanga S.; RadheShyam, A.; Dwivedi, Reena; Rai, A.; Anilkumar, Mettu; Chumbhale, Vilas R.; Aswar, A. S.; Prasad, R. (Indian Journal of Chemical Technology, 2006)
The alkylation ofphenol with methanol was carried out over ZnFe2-xAlxO4 (x = 0, 0.25, 0.5, 0.75 and 1.0) type spinel systems in a Fixed bed, down flow reactor. The influence of Surface acidity, cation distribution in the spinel lattice and various reaction parameters are discussed. A maximum yield of 70.9 and 22.9% with selectivity of 73.5 and 23.3% was obtained for 2,6-xylenol and o-cresol respectively, giving a total ortho selectivity of: 96.8% over ZnFeAlO4 at 350 degrees C, methanol to phenol molar ratio of 5 and WHSV of 0.6 h(-1). Catalyst characterization was made by XRD, Mossbauer spectroscopy, ammonia desorption and BET surface area measurements. Mossbauer spectroscopy reveals isomorphic substitution or Fe 3 by smaller A 13, into the octahedral sites leading to lattice distortion, Unsymmetrical charge distribution and charge transfer from iron to oxygen making it more basic and proton attracting. This helps vertical adsorption ofphenol and formation of 2.6-xylenol. It has been concluded that catalyst acidity plays major role in the reaction as compared to surface area.
Keywords: consecutive methylation; ferrospinels; vertical and horizontal adsorption